Influence of Lechitine Coating in Edible Film of Whey Protein Application at Gouda Cheese Evaluated From Its Water Activity, Adhesion and (Faculty of Animal Science Universitas Brawijaya, 2009)
The aim of this research was to find out the best treatment for the lechitin coating evaluated from water activity, adhesion and microstructure of Gouda cheese surface. Result of the research showed that treatment of lechitin coating at different concentration gave a significant effect ( P<0.05) on water activity of Gouda cheese (0.484±0.0415 – 0.504±0.0408) and didn’t give a significant effect on adhesion (2.470±0.0332 – 2.493±0.0310) edible film of whey protein. Microstructure of Gouda cheese surface showed different picture at every treatment, it was shown with colour indicator at edible film of whey protein. Lechitin 0.6% more able to improve adhesion edible film of whey protein and coating coverage at surface of Gouda cheese, so that Aw of Gouda cheese can inhibit bacteria, mould and yeast growth. Keywords: Lechitin, edible film of whey protein, water activity, adhesion, and microstructure